2019
DOI: 10.1017/s0007123418000595
|View full text |Cite
|
Sign up to set email alerts
|

How Do Observers Assess Resolve?

Abstract: Despite a plethora of theoretical frameworks, IR scholars have struggled with the question of how observers assess resolve. We make two important contributions in this direction. Conceptually, we develop an integrative framework that unites otherwise disconnected theories, viewing them as a set of heuristics actors use to simplify information-rich environments. Methodologically, we employ a conjoint experiment that provides empirical traction impossible to obtain using alternative research designs. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 84 publications
1
33
0
Order By: Relevance
“…In this article, we seek to directly assess the attributes of incidents ordinary citizens use to define incidents as terrorism. We do so using a conjoint experimental design (Hainmueller, Hopkins, and Yamamoto ; Kertzer, Renshon, and Yarhi‐Milo ) in which we present our participants with a series of incidents with randomly generated features and then ask whether they would classify each incident as terrorism. The use of a ratings‐based conjoint design offers two main advantages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we seek to directly assess the attributes of incidents ordinary citizens use to define incidents as terrorism. We do so using a conjoint experimental design (Hainmueller, Hopkins, and Yamamoto ; Kertzer, Renshon, and Yarhi‐Milo ) in which we present our participants with a series of incidents with randomly generated features and then ask whether they would classify each incident as terrorism. The use of a ratings‐based conjoint design offers two main advantages.…”
Section: Methodsmentioning
confidence: 99%
“…See, for example, Malle and Knobe (), Kertzer and McGraw (), and Kertzer, Renshon, and Yarhi‐Milo ().…”
mentioning
confidence: 99%
“…As has been noted elsewhere (Kertzer, Renshon, & Yarhi‐Milo, ), Amazon's Mechanical Turk has grown in popularity in experimental social science. Berinsky, Huber, and Lenz (, p. 366) show that MTurk samples are “often more representative of the general population and substantially less expensive to recruit” than other “convenience samples” often used in political science.…”
Section: Methodsmentioning
confidence: 64%
“…Virtually all experimental designs in IR involve a variety of trade‐offs. For instance, some prefer the approach of asking individuals to take on the perspective of a decision‐maker; however, it has been shown that taking on the perspective of a foreign policy leader results in individuals behaving more hawkishly than they otherwise would (Kertzer & Renshon, ). The hypothetical scenario itself might also be problematic, given its minimal nature; however, the trade‐off is between a short scenario that is easily comprehensible versus a more detailed scenario that might lose the attention of participants.…”
Section: Methodsmentioning
confidence: 99%
“…At the other extreme, we can envision a world in which situational factors always trump dispositional ones and events are independent. In 54 Yarhi-Milo, Kertzer, and Renshon 2018;Kertzer, Renshon, and Yarhi-Milo 2019. 55 Kertzer, Rathbun, and Rathbun 2020.…”
Section: Differences Among Observersmentioning
confidence: 99%